Novel version of the Fibonacci superlattices formed of grapheme nanoribbons: Transmission spectra - Korol, Anatoliy; Litvynchuk (Vorontsova), Svitlana (My University, 2017)
The energy spectra of a novel version of graphene-based Fibonacci superlattices (SL) are calculated. Anew quasiperiodical factor is considered. The SL is built of grapheme nanoribbons and the quasi-periodicity is formed due to the fact that different ribbons are used as individual of the SL and are placed along the lattice growth axis in accordance with the Fibonacci inflation rule. the SL is com posed of smooth-edges and a metal-like armchair NR, and we propose to use a metal-like and a semiconductor armchair NR for another case. Розраховано енергетичні спектри новітньої версії графенових надграток (НГ) Фібоначчі. Розглядається новий квазіперіодичний чинник. НГ побудована із графенових нанострічок, а квазіперіодичність утворюється завдяки тому, що різні стрічки, які використовуються як індивідуальні елементи НГ, розміщено вздовж осі вирощування згідно з інфляційним правилом Фібоначчі. В одному випадку НГ сформовано із стрічок і гладкими краями і металоподібних крісло подібних стрічок, і ми пропонуємо використати металоподібні і напівпровідникові кріслоподібні стрічки в іншому випадку.
Keywords: кафедра фізики та професійної безпеки; graphene; Fibonacci superlattice; velacity barriers; графен; надгратка Фібоначчі; бар’єр швидкості